Isolation and characterization of polyhydroxyalkanoate (PHA) producing bacteria isolate from landfill land of Kampung Jawa Banda Aceh - MAZWAN MAZWAN; FEBRIANI FEBRIANI; NAZARUDDIN NAZARUDDIN (Universitas Syiah Kuala, 2023)
The production of biodegradable plastic from microorganisms has great potential as a substitute for conventional plastic. This study aims to isolate bacterial strains capable of polyhydroxyalkanoates (PHAs) production from the Kampung Jawa landfill land (KJLL) and characterize biopolymers. The bacterial strains were able to produce PHA using a mineral salt medium (MSM) with glucose as a carbon source. The qualitative screening of PHA-producing bacteria was conducted by Sudan Black and Nile Red. Of the 64 bacteria strains, only 41 were able to accumulate PHA in Sudan Black and Nile Red. The results showed that one bacteria the Coccobacillus strain had the highest color intensity for further characterization of PHA. The characterization of PHA by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) showed a melting temperature (Tm) of 101.54°C. X-ray diffraction (XRD) analysis revealed a crystalline structure with an index crystallinity (ICr) value of 15.82% for PHA. The results of the analysis proved that PHA was produced by bacteria isolate. This study suggests that this is the first report of the bacteria from the Kampung Jawa landfill producing PHA with good characteristics and potential biotechnology applications.